Esterifikasi Asam Lemak Menggunakan Katalis Heterogen - Hutagaol, Nurhidayah; Zahrina, Ida; Yelmida, Yelmida (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2020)
Mono-di-acylglycerol (MDG) is a material capable of joining two compounds with different polarities. MDG is a synthetic emulsifier that can be obtained from the esterification reaction of fatty acids with glycerol using organic catalysts, enzyme catalysts, and heterogeneous catalysts. The esterification reaction is a reaction between carboxylic acids and alcohols to produce esters. Esterification reactions generally use inorganic acids such as H2SO4, esterification reactions generally cause corrosion, to inhibit zeolitic catalysts are used. In this journal, heterogeneous catalysts are used, where heterogeneous catalysts occur in more than one phase, the catalyst can be solid in a liquid or a solid in a gas. Catalysts can speed up chemical reactions without changing at the end of the reaction. In general, heterogeneous catalysts are made from transition metal elements because they have good gas-absorbing properties. Keywords: esterification, heterogeneous catalysts, mono-di-asilglyserol.